Fabrication and Characterization of Reconstituted Silk Microgels for the Storage and Release of Small Molecules. Issue 8 (6th March 2019) - Liu, Xizhou; Toprakcioglu, Zenon; Dear, Alexander J.; Levin, Aviad; Ruggeri, Francesco Simone; Taylor, Christopher G.; Hu, Mengsha; Kumita, Janet R.; Andreasen, Maria; Dobson, Christopher M.; Shimanovich, Ulyana; Knowles, Tuomas P. J.
Abstract: Silk fibroin is a natural protein obtained from the Bombyx mori silkworm. In addition to being the key structural component in silkworm cocoons, it also has the propensity to self‐assemble in vitro into hierarchical structures with desirable properties such as high levels of mechanical strength and robustness. Furthermore, it is an appealing biopolymer due to its biocompatability, low immunogenicity, and lack of toxicity, making it a prime candidate for biomedical material applications. Here, it is demonstrated that nanofibrils formed by reconstituted silk fibroin can be engineered into supramolecular microgels using a soft lithography‐based microfluidic approach. Building on these results, a potential application for these protein microgels to encapsulate and release small molecules in a controlled manner is illustrated. Taken together, these results suggest that the tailored self‐assembly of biocompatible and biodegradable silk nanofibrils can be used to generate functional micromaterials for a range of potential applications in the biomedical and pharmaceutical fields. Abstract : Reconstituted silk fibroin nanofibrils are used to generate supramolecular microgels by a soft‐lithography‐based microfluidic approach. The kinetic process of microgel formation has been explored in detail and has been applied to encapsulate small molecules within these microgels. The molecular release‐kinetics for drug‐delivery applications are further evaluated, and it is shown that they are dependent on microgel morphology.